Alcohol Use and Abuse Conspires With HIV Infection to Aggravate Intestinal Dysbiosis and Increase Microbial Translocation in People Living With HIV: A Review - Yan, Jiangyu; Ouyang, Jing; Isnard, Stéphane; Zhou, Xin; Harypursat, Vijay; Routy, Jean-Pierre; Chen, Yaokai (Frontiers in Immunology, 2021)
The intestinal microbiome is an essential so-called human “organ”, vital for the induction of innate immunity, for metabolizing nutrients, and for maintenance of the structural integrity of the intestinal barrier. HIV infection adversely influences the richness and diversity of the intestinal microbiome, resulting in structural and functional impairment of the intestinal barrier and an increased intestinal permeability. Pathogens and metabolites may thus cross the “leaky” intestinal barrier and enter the systemic circulation, which is a significant factor accounting for the persistent underlying chronic inflammatory state present in people living with HIV (PLWH). Additionally, alcohol use and abuse has been found to be prevalent in PLWH and has been strongly associated with the incidence and progression of HIV/AIDS. Recently, converging evidence has indicated that the mechanism underlying this phenomenon is related to intestinal microbiome and barrier function through numerous pathways. Alcohol acts as a “partner” with HIV in disrupting microbiome ecology, and thus impairing of the intestinal barrier. Optimizing the microbiome and restoring the integrity of the intestinal barrier is likely to be an effective adjunctive therapeutic strategy for PLWH. We herein critically review the interplay among HIV, alcohol, and the gut barrier, thus setting the scene with regards to development of effective strategies to counteract the dysregulated gut microbiome and the reduction of microbial translocation and inflammation in PLWH.